Altered vascular smooth muscle cell differentiation in the endometrial vasculature in menorrhagia - Biswas Shivhare, Sourima; Bulmer, Judith N; Innes, Barbara A; Hapangama, Dharani K; Lash, Gendie E (Human reproduction (Oxford), 2014)
How does the smooth muscle content and differentiation stage of vascular smooth muscle cells (VSMCs) in endometrial blood vessels change according to the different phases of the menstrual cycle and is this altered in women with menorrhagia? The smooth muscle content (as a proportion of the vascular cross-sectional area) of endometrial blood vessels remained unchanged during the normal menstrual cycle and in menorrhagia; however, expression of the VSMC differentiation markers, smoothelin and calponin, was dysregulated in endometrial blood vessels in samples from women with menorrhagia compared with controls. Menorrhagia affects 30% of women of reproductive age and is the leading indication for hysterectomy. Previous studies have suggested important structural and functional roles for endometrial blood vessels, including impaired vascular contractility. Differentiation of VSMC from a synthetic to contractile state is associated with altered cellular phenotype that contributes to normal blood flow and pressure. This vascular maturation process has been little studied in endometrium both across the normal menstrual cycle and in menorrhagia. Endometrial biopsies were taken from hysterectomy specimens or by pipelle biopsy prior to hysterectomy in controls without endometrial pathology and in women with menorrhagia (n = 7 for each of proliferative, early-secretory, mid-secretory and late-secretory phases for both groups). Biopsies were formalin fixed and embedded in paraffin wax. Paraffin-embedded sections were immunostained for α smooth muscle actin (αSMA), myosin heavy chain (MyHC), H-caldesmon, desmin, smoothelin and calponin (h1 or basic). VSMC content was measured in 25 αSMA(+) vascular cross sections per sample and expressed as a ratio of the muscular area:gross vascular cross-sectional area. VSMC differentiation was analysed by the presence/absence of differentiation markers compared with αSMA expression. Smoothelin and calponin expression was also analysed in relation to total number of blood vessels by double immunostaining for endothelial cell markers. Study of VSMC differentiation markers revealed decreased expression of calponin both in αSMA(+) vessels (P = 0.008) and in relation to total number of vessels (P = 0.001) in late secretory phase endometrium in menorrhagia compared with controls. Smoothelin expression in αSMA(+) vessels was increased (P = 0.03) in menorrhagia, although this was not significant in relation to the total number of vessels. In normal endometrium, the proportion of blood vessels expressing αSMA increased from 63% in proliferative endometrium to 81% in the late secretory phase (P = 0.002). The overall arterial muscle content did not differ between control and menorrhagia at any phase of the menstrual cycle, occupying 78-81% of gross vascular cross-sectional area during the different menstrual cycle phases. This study included both straight and spiral arterioles and analysed only stratum functionalis. The VSMC differentiation with respect to αSMA expression is an observational study and the data are presented as presence or absence of the differentiation markers in each field of view, corresponding with the vascular cross sections included in the study of vascular muscle content. Smoothelin and calponin have been widely implicated as important regulators of vascular tone, vascular contractility and rate of blood flow. Our results have uncovered a disparate pattern of calponin expression, potentially indicating a dysfunctional contraction mechanism in the endometrial blood vessels in menorrhagia, thus implicating calponin as a potential therapeutic target. This study was funded by Wellbeing of Women (RG1342) and Newcastle University. There are no competing interests to declare. Not applicable.